Supervisor Feedback, Ergonomics and Job Performance: A Study at One of Malaysia’s Frontline Government Agency - Omar, Muhamad Khalil; Dahalan, Noor Azura; Mohd, Idaya Husna; Shah, Maimunah Mohd; Azman, Nurul Nadiah Mohammad (International Journal of Economics and Financial Issues, 2016)
A well-managed organization usually sees an average worker as the root source of quality and productivity gains. Such organizations do not look to capital investment, but to employees, as the fundamental source of improvement. Therefore, in order to increase employee performance, many factors such as supervisor feedback and ergonomics are very important especially for organization that involves frontline staffs who has to entertain customers all the time. Hence, this study focuses on effect of supervisor feedback and ergonomics towards job performance among employees at one of Malaysia’s frontline government agency. The study was quantitatively conducted using standardized questionnaires that was participated by 82 respondents. The results showed that supervisor feedback and ergonomic were significantly and positively impacted job performance. Thus, this study provides references to academics and practitioners on the effectiveness of giving quality feedback and good ergonomically working conditions towards improving performance of frontline staffs. Keywords: Supervisor Feedback; Ergonomics; Job Performance JEL Classifications: M54; M12